Accessibility Relations of Possible Worlds of the Fantastic - Ariza Trinidad, Eva (2023)
One of the issues addressed in possible worlds semantics is the accessibility relations of fictional worlds, that is, how these worlds relate to the real world. This paper takes the works by authors such as Kendall Walton, Marie-Laure Ryan and Tomás Albaladejo as a starting point to examine those features of the fantastic which constitute accessibility relations in two ways: those that shape the world out of real entities, such as the representation of macrostructural models or the incompatibility of elements, and those that intervene in the access of fictional entities to the real world, such as the presentation of verisimilitude and authentication.